Critical control points in the packaging step in a roasted and ground coffee industry (Research, Society and Development, 2022)
The Brazilian food and beverage industry is the largest in the country, contributing significantly to the economy, with emphasis on coffee consumption products. In this scenario, this research aimed to evaluate the Hazard Analysis and Critical Control Points system in a roasted and ground coffee industry in Salvador, Bahia A cross-sectional, diagnostic and intervention study was conducted in the Company's packaging sector, between February and September 2021. Information collection was performed from the collection of secondary data, through a computational tool that performs a Checklist based on the requirements of ISO 22000 and ISO/TS 22002-1. The study showed a general acquiescence of 87.2%, with emphasis on the items: Food defense (100%), health and hygiene (100%) and zoning (91.62%). On the other hand, the items: Cleaning and organization of the site (57.27%) and Records (68.75%) were classified as less appropriate. Regarding intervention actions, Action Plans were elaborated and monitored with a multidisciplinary team, as a way to correct and prevent failures in the food safety system. After diagnosis and intervention, it was found that the biological hazards were those that require the most attention, because the means of contamination are more frequent when compared to physical and chemical hazards. These results indicate that the food safety team should develop strategies and develop behaviors to motivate the operational team to try to apply procedures related to the biological safety of the product.